AN ASSESSMENT STUDY OF MATERNAL MORTALITY RATIO DATABANK IN FIVE DISTRICTS OF NORTH WESTERN FRONTIER PROVINCE PAKISTAN - Farooq, Nasir; Jadoon, Huma; Masood, Tayyeb Imran; Wazir, M Saleem; Farooq, Umer; Lodhi, Mohammad Saqib (Journal of Ayub Medical College Abbottabad, 2006)
Background: Maternal mortality ratio is an indicator to measure the summary of information about mother and child health. It is estimated that about 500 maternal deaths occur per 100,000 live births each year in Pakistan. It is a well known fact that all health statistics coming out of the developing countries are calculated guesstimates some are perhaps more close to the real figures than the others. There is a dire need to help generate information that can be used by health professionals, health care planners and managers to save women’s lives by improving the quality of care provided to turn away maternal mortality. The maternal mortality ratio for Pakistan as well as for NWFP is projected as 533 /100,000 live births for the year 1990-91 produced by National Institute of Population Studies, Pakistan. Methods: This was a retrospective cross-sectional quantitative study for the period (2001-2002) conducted in five districts of (NWFP) North Western Frontier Province, Pakistan. Results: National HMIS data opened the maternal mortality ratio for; Haripur as 0.168 and 0.173, Mansehra 00 and 00, Battagram 00 and 00, Swat 0.051 and 0.524 and Swabi 00 and 0.968 per/1000 live births, respectively. The small part exercise outcome (the study) endorsed more shadowy side of the actual maternal mortality ratio for the same period in the same districts. Conclusion: In our country there is a urgent need to institute an efficient mode of operation to get accurate maternal mortality database. Verbal Autopsy method is cost effective and feasible approach for implementation in a country like Pakistan. Key Words: Maternal mortality, Verbal Autopsy